1985
DOI: 10.1093/jnci/75.5.859
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Among a Large Cohort of Chemical Manufacturing Employees

Abstract: Cause-specific mortality was surveyed among 19,608 male employees with 1 or more years of service between 1940 and 1980 at the Texas Operations of Dow Chemical U.S.A. Vital status was ascertained through 1980 for 97.3% of the cohort members, and death certificates were obtained for 96.4% of the 3,444 decedents. Mortality risks were found to vary, depending upon which of 3 population groups (United States, Texas, and local counties) was used for comparison, although significantly fewer than expected deaths from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…While the earlier study reported an elevated nonsignificant SMR of 145 (95%CI ϭ 90-222) for senility and ill-defined conditions among white males, the update showed a significant SMR of . This finding is consistent with elevations reported for this category in other industrial studies in this region of the United States and is explainable by local death certification practices [Bond et al, 1985;Olsen et al, 1994].…”
Section: Discussionsupporting
confidence: 92%
“…While the earlier study reported an elevated nonsignificant SMR of 145 (95%CI ϭ 90-222) for senility and ill-defined conditions among white males, the update showed a significant SMR of . This finding is consistent with elevations reported for this category in other industrial studies in this region of the United States and is explainable by local death certification practices [Bond et al, 1985;Olsen et al, 1994].…”
Section: Discussionsupporting
confidence: 92%
“…Six of the seven deaths in this category occurred among employees from the Texas facility. The state of Texas is known to have an abnormally high death rate from symptoms, senility and ill-defined conditions, and this regional phenomenon appears to be the most likely explanation for the finding in this cohort (6).…”
Section: Discussionmentioning
confidence: 73%
“…The method of the study cohort identification has been reported in detail elsewhere [Bond et al, 1985b]. Briefly, all Texas Operations employees located in the Brazosport area (Freeport, Texas) who had 1 or more years of service since January 1 , 1940, were eligible for inclusion in a Texas Operations vital status registry.…”
Section: Methodsmentioning
confidence: 99%
“…The cohort has been updated periodically throughout the 1980s based on computerized company records. Besides the Freeport, Texas location (Plants A and B) that was studied in the original report by and Bond et al [1985b], the nearby Oyster Creek site of Texas Operations was also included in the present study. The historic census for Oyster Creek was determined by review of plant rosters, work history records, and computer personnel files.…”
Section: Methodsmentioning
confidence: 99%